2014
DOI: 10.1111/1468-0009.12061
|View full text |Cite
|
Sign up to set email alerts
|

How Successful Is Medicare Advantage?

Abstract: Context: Medicare Part C, or Medicare Advantage (MA), now almost 30 years old, has generally been viewed as a policy disappointment. Enrollment has vacillated but has never come close to the penetration of managed care plans in the commercial insurance market or in Medicaid, and because of payment policy decisions and selection, the MA program is viewed as having added to cost rather than saving funds for the Medicare program. Recent changes in Medicare policy, including improved risk adjustment, however, may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 60 publications
4
82
0
2
Order By: Relevance
“…A subsidy equal to costs in TM is sufficient to finance a negative premium for most plans, since MA plans are, on average able to provide the same benefits as TM at lower cost (Newhouse and McGuire, 2014). When the Medicare subsidy exceeds the MA plan's bid, which is supposed to be a declaration of its costs, the plan must either increase benefits to beneficiaries (by, for example, reducing the demand-side cost sharing from that in TM) or reduce the premium charged to beneficiaries.…”
Section: Medicare Advantage (Us)mentioning
confidence: 99%
“…A subsidy equal to costs in TM is sufficient to finance a negative premium for most plans, since MA plans are, on average able to provide the same benefits as TM at lower cost (Newhouse and McGuire, 2014). When the Medicare subsidy exceeds the MA plan's bid, which is supposed to be a declaration of its costs, the plan must either increase benefits to beneficiaries (by, for example, reducing the demand-side cost sharing from that in TM) or reduce the premium charged to beneficiaries.…”
Section: Medicare Advantage (Us)mentioning
confidence: 99%
“…McGuire et al (2011) review the economic history of Medicare Advantage and find that Medicare Advantage generally cost more than the traditional Medicare program. Newhouse and McGuire (2014) suggest that, on average, Medicare Advantage plans appear to offer higher value than the Original Medicare, and greater Medicare Advantage penetration appears to improve the performance of the Original Medicare. Landon et al (2012) compare utilization patterns of enrollees in Medicare Advantage plans and the traditional Medicare.…”
Section: Comparative Literature On Acos and Medicare Advantagementioning
confidence: 99%
“…With rising payments and expanded benefits, as well as more recent evidence showing that MA outperforms traditional Medicare on various quality measures, MA has become a welfare-expanding and welfare-improving program (Ayanian et al 2013a;Ayanian et al 2013b;Newhouse and McGuire 2014). The financial protections and improving quality has helped to broaden support and increase the political legitimacy of the program.…”
Section: Beneficiariesmentioning
confidence: 99%
“…A 2006 report from the Commonwealth Fund showed that in a sample of 88 MA plans, the out-of-pocket (OOP) costs were lower in nearly every MA plan than they would have been had a beneficiary enrolled in traditional Medicare (Biles, Nicholas, and Guterman 2006a). 3 In addition to greater protections against financial risk, recent evidence shows that in areas where comparable data is available, MA has outperformed traditional Medicare on various measures of quality and appropriateness of care (Newhouse and McGuire 2014). Beneficiaries enrolled in MA HMOs, for example, were consistently more likely to receive appropriate breast cancer screenings, diabetes care, and cholesterol testing for cardiovascular disease, as well as have higher rates of influenza and pneumococcal vaccines (Ayanian et al 2013b;Newhouse and McGuire 2014).…”
Section: Beneficiariesmentioning
confidence: 99%
See 1 more Smart Citation